2018
DOI: 10.5858/arpa.2018-0219-ra
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto Disease: A Review

Abstract: Kikuchi-Fujimoto disease (KFD) is a rare entity characterized by subacute necrotizing lymphadenopathy and frequently associated with fever. Young adults of Asian ancestry are most commonly affected, but it has been reported worldwide. Despite many studies in the literature, the cause of KFD remains uncertain. Histologically, KFD is characterized by paracortical lymph node expansion with patchy, well-circumscribed areas of necrosis showing abundant karyorrhectic nuclear debris and absence of neutrophils and eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
261
0
34

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(304 citation statements)
references
References 33 publications
9
261
0
34
Order By: Relevance
“…Kikuchi-Fujimoto disease, also known as histiocytic necrotizing lymphadenitis, was first described in 1972 [1]. It is a rare self-limiting lymphadenopathy, more commonly described in females, those aged 20-40 years and are of Southeast Asia origin [2,3]. Although less common within the African population, a few cases of the disease have been reported from Gabon, Senegal, Morocco, and Tunisia [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kikuchi-Fujimoto disease, also known as histiocytic necrotizing lymphadenitis, was first described in 1972 [1]. It is a rare self-limiting lymphadenopathy, more commonly described in females, those aged 20-40 years and are of Southeast Asia origin [2,3]. Although less common within the African population, a few cases of the disease have been reported from Gabon, Senegal, Morocco, and Tunisia [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al identified CMV,EBV, HHV-6, HHV-7, Parvovirus B19, and mycobacterial species from lymph node samples of 153 patients in China with KFD [9]. KFD has been described in association with SLE, Still's disease, Wegener's granulomatosis, Graves' disease, and Sjogren's disease [3]. Tanaka et al found higher frequencies of the HLA DPA1 * 01 and DPB1 * 0202 allele in Japanese patients with KFD [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common region of lymph node involvement is posterior cervical (60% -90% of cases) and frequently occurs with concomitant involvement of axillary and/or supraclavicular lymph nodes. Generalized lymphadenopathy, however, is rarely reported [2,5,[8][9]. Intra-abdominal regions have also been reported with unknown frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphadenopathy is most frequently associated with fever and other less commonly reported signs and symptoms, including weight loss, vomiting, headache, arthralgia, night sweats, sore throat, hepatosplenomegaly, and cutaneous lesions [2,[8][9]. Cutaneous eruptions in KFD occur in about 40% of cases with reported manifestations, including urticarial-like lesions, generalized erythema and papules, plaques and nodules, leukocytoclastic vasculitis, erythema multiforme, indurated erythematous lesions, oral ulcerations, alopecia, and malar erythema [2,5,9,[11][12]. Furthermore, the cutaneous manifestations of KFD could be consistent with cutaneous manifestations of SLE [13].…”
Section: Discussionmentioning
confidence: 99%